Mineralizers in uranium ore albitites of the Ukrainian Shield - Fomin, Yu.A.; Verhovcev, V.G.; Demikhov, Yu.N.; Studzinska, A.O. (Reports of the National Academy of Sciences of Ukraine, 2017)
For the first time, the main mineralizers of the complex of uranium ore deposits for the albitite formation of the Ukrainian Shield have been studied, which gives possibilities of the use of genetic methods. This approach allowed a more detailed trace of the mineralization under conditions of the increased oxygen fugacity in alkaline metasomatic fluids. The mineralizing system during the sodium metasomatosis operated in the mode of multiple interaction of the formational (interstitial) fluid and meteoric waters enriched by uranium. It is also confirmed by the genetic linkage of the uranium mineralization with carbonate complexes of uranium as a form of transport.